The Director’s Role in the Production of the Biographical Documentary Film of a Deaf Individual Titled “Merakit dalam Sunyi” - Indra Dwiyana; Arrya Dianta (CV Projurnal Mitra Publikasi, 2025)
The persistent inequality experienced by persons with disabilities in Indonesia is reinforced by limited informative media representation. Digital platforms such as YouTube are dominated by entertainment-oriented content, leaving minimal space for educational materials that raise awareness about the deaf community. This project seeks to address this gap through the production of “Merakit dalam Sunyi” or in English called Assembling in Silence, a biographical documentary portraying the life of Ria, a deaf online motorcycle taxi driver. The film aims to shift public perceptions, educate audiences about the capabilities of deaf individuals, and provide an informative alternative within digital media spaces. The production employed a conventional three-stage workflow: pre-production (research, script development, and planning), production (four days of field shooting), and post-production (editing and finalization). The resulting documentary offers an audio-visual depiction of how deaf individuals can work and live independently despite social barriers. The project concludes that documentary media can function as an effective instrument for fostering social inclusion by delivering both information and motivation to the public. It also underscores the director’s central role in shaping the work from initial concept to final edit.